2020
DOI: 10.1016/j.ecoleng.2020.105927
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a full scale constructed wetland as ecological practice for agricultural drainage water treatment in Northern Italy

Abstract: Non-point sources of pollution, primarily agricultural drainage waters, can cause eutrophication and deterioration of water bodies. Surface flow constructed wetlands (SFCWs) are an ecological solution that can represent an efficient barrier and prevent agricultural pollutants from reaching other ecosystems. However, to better manage them and to understand removal processes occurring, it is important to study SFCWs that are functioning for longer periods of time and assess their efficiencies. This study concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 56 publications
(88 reference statements)
3
18
0
Order By: Relevance
“…For instance, Tanner (1996) conducted a study using eight emergent macrophyte species ( Cyperus involucratus , Phragmites australis, Choenoplectus validus, Glyceria maxima , Baumea articulata , Juncus effuses , Bolboschoenus fluviatilis , and Zizania latifolia ) and found that nitrogen uptake in the above‐ground tissues of the species ranged from 15 to 32 mg/g was 65–92% of total nitrogen removed in CWs. Recently, similar findings were reported by Lavrnić et al (2020) in Italy. In SFCW, Lavrnić et al (2020) observed that the total nitrogen uptake range from 19 to 26.3 g/m 2 was 46–70% of total inflow nitrogen in CWs.…”
Section: Classification Of Cwssupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, Tanner (1996) conducted a study using eight emergent macrophyte species ( Cyperus involucratus , Phragmites australis, Choenoplectus validus, Glyceria maxima , Baumea articulata , Juncus effuses , Bolboschoenus fluviatilis , and Zizania latifolia ) and found that nitrogen uptake in the above‐ground tissues of the species ranged from 15 to 32 mg/g was 65–92% of total nitrogen removed in CWs. Recently, similar findings were reported by Lavrnić et al (2020) in Italy. In SFCW, Lavrnić et al (2020) observed that the total nitrogen uptake range from 19 to 26.3 g/m 2 was 46–70% of total inflow nitrogen in CWs.…”
Section: Classification Of Cwssupporting
confidence: 88%
“…Koottatep and Polprasert (1997) reported that plants in CWs can effectively remove 66%–71% of total nitrogen through plant uptake. Globally, several studies have reported the nitrogen removal that occurred through uptake and assimilation in CWs (Gottschall et al, 2007, Jampeetong et al, 2012, Lavrnić et al, 2020, Maltais‐Landry et al, 2009, Nandakumar et al, 2019, Nilsson et al, 2020, Nitrogen & Wetlands, n.d.; Pincam et al, 2020, Tao, 2018, Vymazal, 2007, Vymazal & Kro, 2009, Zhang et al, 2016). In some studies, a positive correlation between the plant biomass and N uptake was observed.…”
Section: Classification Of Cwsmentioning
confidence: 99%
“…As transition zones between terrestrial and aquatic environments [39], CWs are perceived as a cost-effective (low-cost and straightforward construction, operation and maintenance reduced costs, or energy biomass production) [40] and ecological and sustainable technology for treating different types of wastewater without the input of fossil fuels [41]. Likewise, CWs can contribute to flooding risk mitigation, stormwater runoff management, and increase water supply [42] by constituting an alternative option to conventional wastewater treatment plants (WWTPs) [43].…”
Section: Introductionmentioning
confidence: 99%
“…Full‐scale application of the floating wetlands is reported by Lavrnic et al. (2020) [42] but with inconsistent P removal efficiency due to the rain precipitation effect. A subsequent P‐recovery from biomass is a valid option.…”
Section: P In Agricultural Runoffs and Crop Residuesmentioning
confidence: 99%